Comparação do desempenho físico e recuperação muscular entre vegetarianos e onívoros - Souza, Alice Conrado de (2019)
Due to higher food intake with antioxidant potential, vegetarian diets may have an advantage in cardiorespiratory performance; however, the low proteins and amino acids intake may impair the strength and muscle power production and may be detrimental to athletes and exercisers recovery. The aim of this study was compare physical performance among physically active individuals adhering to the ovolactovegetarian, vegan and omnivorous diet and recovery of exercise-induced muscle damage (EIMD) between vegans (VEGAN) and omnivores (ONI). Thus, two studies were carried out. In the study one, ovalactovegetarians (OVLA), VEGAN and ONI performed maximum aerobic velocity (VAM), 10 maximum repetitions test (10RM), handgrip strength, deadlift strength and countermovement jump (CMJ) tests; and responded to the 24-hour food recall. VEGAN, OVLA and ONI did not show differences in strength tests (i.e. 10RM: 62 ± 25 vs 70 ± 12 vs 60 ± 27 kg), CMJ (43.83 ± 7.41 vs 46.21 ± 10.28 vs 46, 34 ± 11.99 cm) and VAM (15.82 ± 1.45 vs. 15.62 ± 2.31 vs. 14.48 ± 2.17 km / h) even with a difference in nutrient intake (i.e. ONI: 1801 ± 377 vs. VEGAN: 2430 ± 632 kcal). Thus, the diet VEGAN, OVLA and ONI are similar in physical performance. In the two study, 14 vegans and omnivores underwent a protocol of EIMD and were evaluated before, immediately after, 24, 48 and 72 hours with CMJ , range of motion (WMD) tests, blood concentration of creatine kinase (CK) and lactate dehydrogenase (LDH), muscle soreness (DOMS), thigh circumference (CCx) and responded to the 24-hour food recall. VEGAN showed 4% reduction in CMJ, whereas omnivores increased the jump by 6% in the 72 hours after the DMIE in relation to the baseline values. Greater DOMS was found for VEGAN at 24h and 72h after EIMD compared to ONI. There was lower ranched chain amino acids ingestion by vegans (ONI: 23.73 ± 8.25 vs. VEGAN: 9.26 ± 2.05 g). Thus, it is possible to conclude that vegans may present muscle recovery damages after EIMD in relation to omnivores.